Is left ventricular hypertrophy a friend or foe of patients with aortic stenosis? - Davies, Cecilla; Zerebiec, Katherine; Rożanowska, Agnieszka; Czestkowska, Ewa; Długosz, Dorota; Chyrchel, Bernadeta; Surdacki, Andrzej (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2018)
Left ventricular hypertrophy (LVH) is traditionally considered a physiological compensatory response to LV pressure overload, such as hypertension and aortic stenosis (AS), in an effort to maintain LV systolic function in the face of an increased afterload. According to the Laplace law, LV wall thickening lowers LV wall stress, which in turn would be helpful to preserve LV systolic performance. However, numerous studies have challenged the notion of LVH as a putative beneficial adaptive mechanism. In fact, the magnitude of LVH is associated with higher cardiovascular morbidity and mortality, especially when LVH is disproportionate to LV afterload. We have briefly reviewed: first, the importance of non-valvular factors, beyond AS severity, for total LV afterload and symptomatic status in AS patients; second, associations of excessive LVH with LV dysfunction and adverse outcome in AS; third, prognostic relevance of the presence or absence of pre-operative LVH in patients referred for aortic valve surgery; fourth, time course, determinants and prognostic implications of LVH regression and LV function recovery after surgical valve replacement and transcatheter aortic valve implantation (TAVI) with a focus on TAVI-specific effects; fifth, the potential of medical therapy to modulate LVH before and after surgical or interventional treatment for severe AS, a condition perceived as a relative contraindication to renin-angiotensin system blockade.